Beware the pancreatic incidentaloma in colorectal tumours: pancreatic adenocarcinoma with metastases to the colon and rectum. Issue 1 (24th January 2022) - O'Sullivan, Brian; Burton, Thomas; Van Dalen, Ralph; Welsh, Fraser; Pandita, Archana; Fischer, Jesse
Abstract: Colorectal cancer (CRC) is the third most diagnosed malignancy in the Western world. Routine staging of CRC often identifies incidental lesions on cross-sectional imaging. Appropriate treatment is dependent on a correct histological diagnosis. Pancreatic Ductal Adenocarcinoma (PDAC) is a rarer and often devastating diagnosis for which the treatment pathway differs significantly to CRC. We report two rare cases: the first recorded case of PDAC with synchronous rectal metastasis and a case of an acute presentation with large bowel obstruction from synchronous colonic metastasis. Both cases presented a significant diagnostic challenge. The management of both cases would have been altered had the histological diagnosis been known prior to surgery. Clinicians treating CRC should be wary of incidental lesions on staging investigations as they rarely represent an occult extra-intestinal primary malignancy. Immunohistochemistry plays an important role in ascertaining the origin of gastrointestinal malignancy.